Penerapan Sistem Pemesanan Paket Wisata Berbasis Website untuk Memudahkan Proses Pemesanan pada “Ngetour” Organizer - Dede Darsono; Luthvia Damayanti (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
This research aims to develop a website-based tour package booking system to improve the efficiency and effectiveness of the reservation process at “Ngetour” Organizer, which currently relies on conventional methods. At present, customers must place bookings through WhatsApp, and all reservation data are recorded manually by the admin. This approach is considered less efficient, particularly when the number of participants increases, as it is prone to human error, data duplication, and mismatched information. Such limitations may affect service quality and overall business performance.To address these issues, a web-based information system is designed to streamline the reservation process and support better business management. The system enables customers to browse tour packages, submit bookings, and complete payments more conveniently, while allowing administrators to manage orders and monitor transactions in a structured and organized manner. The development process applies the Rapid Application Development (RAD) methodology to ensure faster and more flexible system creation. The application is built using the PHP programming language with the CodeIgniter framework and MySQL database. Based on black box testing and User Experience Questionnaire (UEQ) evaluation, the system effectively improves booking management and user satisfaction